PENGARUH PEMBELAJARAN KONTEKSTUAL DENGAN STRATEGI REACT TERHADAP KEMAMPUAN KONEKSI MATEMATIKA - Fadhila, Fadhila; Trisoni, Ridwal; Afriyani, Dona (Jurnal Pembelajaran MIPA, 2014)
The purpose of this research was to determine whether the ability of mathematical connections with students through contextual teaching and learning REACT strategy is better than the ability of students to learn mathematical connection with conventional learning. This research is a quasi-experimental design with a randomized control group design only. Research procedures can be divided into three phases: preparation, implementation phase and the completion phase. The research instrument used is the mathematical connection ability tests. The hypothesis was tested with the help of MINITAB using one-way t-test. The conclusion of this study is the ability of students in the application of mathematical connections contextual teaching and learning with REACT strategy is better than the ability of mathematical connections in the control classes.Â Key words: contextual teaching and learning with REACT strategy, the ability of mathematical connections